Interference management and spectrum sharing in integrated satellite-terrestrial networks: progress, key technologies and future directions - ZHU Jianfeng; SUN Yaohua; FENG Xin’ao; PENG Mugen (Dianxin kexue)
Due to the advantages in coverage and cost-effectiveness, low earth orbit satellites can provide supplemental coverage for terrestrial networks. Therefore, integrated satellite-terrestrial networks have emerged as a promising solution to achieve ubiquitous global connectivity. However, facing the challenges caused by the scarcity of spectrum resources and complex interference, effective interference management and spectrum sharing were the critical aspects of integrated satellite-terrestrial networks. Firstly, recent research progress and a comprehensive exploration of challenges for different interference scenarios were introduced. Then, to overcome the shortage of existing research, several potential and innovative technical solutions were presented, whose performance was verified by simulations. Finally, several potential future technical directions were discussed for integrated satellite-terrestrial networks.